Optimizing Cork Oak (Quercus suber) Acorn Growth and Survival: Influence of Harvest Timing and Nursery Conditions in Morocco - Mabrouk, Achraf; Souileh, Ayoub; Oubrahim, Hayat; Magri, Najib; El Antry, Salwa; Abidi, Fatima; Zekhnini, Oussama; Abbas, Younes; Ouajdi, Mohamed (Journal of Multidisciplinary Applied Natural Science, 2025)
Cork oak (Quercus suber) forests are vital for maintaining ecological balance and supporting socio-economic stability in Morocco. However, these forests face significant degradation driven by climate change, human activities, and inadequate regeneration practices. A critical factor influencing successful cork oak regeneration is the timing of acorn harvesting, which directly impacts germination rates and seedling quality. This study aimed to determine the optimal acorn harvesting periods to maximize germination and produce robust seedlings suitable for nursery and field planting. Conducted at the Center for Innovation, Research and Training under the National Agency for Water and Forests, the research involved collecting acorns from the Maâmora forest across six harvesting periods: August, September, early-October, mid-October, November, and December. The methodology included acorn sorting, phytosanitary treatments, and standardized nursery substrate preparation. Key parameters such as germination rate, seedling height, collar diameter, survival rate, and root system development were systematically monitored. Results indicated that acorns harvested in mid-October and November yielded the highest germination rates (86% and 85%, respectively), superior seedling growth (average heights of 21.40 cm and 10.09 cm), and better survival rates (95% and 75%). In contrast, acorns harvested in August showed the lowest germination (50%) and reduced seedling vigor, reflecting the detrimental effect of immature acorns. Early harvests in August and September corresponded with slower growth and lower survival. The findings underscore the critical influence of harvest timing on cork oak regeneration success. Acorns collected during mid-October and November demonstrated faster germination, enhanced seedling vigor, and robust root development. The study recommends focusing on these optimal harvesting windows, combined with proper storage and nursery management, to improve reforestation efforts and support the sustainable restoration of Morocco’s cork oak ecosystems.